2015
DOI: 10.1039/c5dt01640a
|View full text |Cite
|
Sign up to set email alerts
|

Unusual coordination state of cobalt ions in zeolites modified by aluminum chloride

Abstract: Co- and Al-modified zeolites (Al-Co-ZSM-5) were prepared by solid-state ion exchange with cobalt acetate or chloride, followed by AlCl3 immobilization from anhydrous toluene solution. Based on data from XRD, X-ray absorption (XANES/EXAFS), X-ray photoelectron spectroscopy and DRIFT spectral studies of adsorbed probe molecules (carbon monoxide, ethane), a new cobalt electronic state, bonded with surface aluminum atoms through oxygen and chlorine atoms, arises on the surface of Al-Co-ZSM-5. A new band at 2192 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…59,60 It has been proved that the adsorption of light alkanes by metal oxides in the form of cations results in the change of relative intensity distribution of absorption bands, which largely depends on the properties of cations and metallic oxides. 60 According to the adsorption strength of ethane on all samples, it is found that Fe2O3-C is easier to adsorb water than ethane. However, compared with water, it has stronger adsorption for ethane on Fe2O3-S and Fe2O3-R.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 It has been proved that the adsorption of light alkanes by metal oxides in the form of cations results in the change of relative intensity distribution of absorption bands, which largely depends on the properties of cations and metallic oxides. 60 According to the adsorption strength of ethane on all samples, it is found that Fe2O3-C is easier to adsorb water than ethane. However, compared with water, it has stronger adsorption for ethane on Fe2O3-S and Fe2O3-R.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the main lines, the spectra exhibit intense “shake‐up” satellites at higher binding energies, which are characteristic of Co II . To analyze the relative content of different Co species on the surface and in the volume of the zeolite, Co 2p 3/2 peaks and their satellites were decomposed into four components as described in Refs, taking into account that Co 2p 3/2 binding energies of Co II and Co III main components are 782.1±0.1 eV (peak I in Figure a) and 779.8±0.1 eV (peak II in Figure a), respectively. The contents of Co II and Co III in mono‐ and bimetallic samples are given in Table .…”
Section: Resultsmentioning
confidence: 91%
“…DRIFTS of adsorbed CO . IR spectra of chemisorbed CO are widely used to find an electronic state of metal …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations